COVID-19 impacts and response in Juneau Alaska 2022 - James Powell; Sean Asiqłuq Topkok; Robert Orttung (Arctic Data Center, 2022)
The data set contains written transcripts from 50 local key informant interviews in real time about the early phases of COVID-19 impacts and adaptive responses taken by the City and Borough of Juneau, Alaska USA. During the early phases of the pandemic (2020) key informants, including healthcare professionals, elected officials, local government managers, and Indigenous peoples, provided in-depth insights and local and Indigenous knowledge and information about their organizations and community response. Tlingit and Haida people interviewed for this project stressed the themes of resiliency, worldview, cultural values and knowledge, and adaptation. The transcripts served as primary sources and evidence for our research findings published in the State and Local Government Review.